Analysis of livelihood activity amongst itinerant west African migrant traders in the Accra metropolitan area - Elijah Yendaw; Augustine Tanle; Akwasi Kumi-Kyereme (Journal of Global Entrepreneurship Research, 2019)
In West Africa, studies on migration and livelihoods are mostly limited to internal migrants. This study analyzed the livelihood activities of itinerant West African migrant traders in the Accra Metropolitan Area, using mixed methods approach. The study which was guided by the framework for migration and itinerant migrant trade surveyed 779 itinerant immigrant traders and interviewed 12 key informants. Descriptive statistics and binary logistic regression were the main analytical techniques used. The results showed that most of the immigrant traders were young, unmarried males with no formal education and their main trading activity was itinerant retailing of foot wears/leather belts/bags and herbal medicines. As regards their livelihood status, female immigrant traders and those who were younger (< 20 years) were less likely to have improved livelihood status. Moreover, while immigrant traders of food products were more likely to have a deteriorated livelihood status, those engaged in the sale of durable products (electronics and accessories) were most likely to achieve improved livelihood status. The study recommends that itinerant West African migrant traders should invest more of their resources in the sale of electronics and accessories as it has the highest potential of guaranteeing secured and improved livelihoods. Any form of business support aim at improving the livelihood status of itinerant immigrant traders should be focused on young and female itinerant traders and those engaged in the sale of food-related items because they were less likely to maintain improved livelihood status.
Keywords: 650; Accra metropolitan area; Livelihood activity; West African migrants